CircHIPK3 Promotes Metastasis of Gastric Cancer via miR-653-5p/miR-338-3p-NRP1 Axis Under a Long-Term Hypoxic Microenvironment - Jin, Yue; Che, Xiaofang; Qu, Xiujuan; Li, Xin; Lu, Wenqing; Wu, Jie; Wang, Yizhe; Hou, Kezuo; Li, Ce; Zhang, Xiaojie; Zhou, Jianping; Liu, Yunpeng (Frontiers in Oncology, 2020)
As a vital feature of the microenvironment, hypoxia, especially long-term hypoxia, is known to promote metastasis and lead to poor prognosis in solid tumors. Circular RNAs (circRNAs) participate in important processes of cell proliferation and metastasis in cancers. However, the contribution of circRNAs to metastasis under long-term hypoxia is obscure. In this study, we aim to explore specific functions of circHIPK3 in longterm hypoxia-promoting metastasis of gastric cancer (GC). The hypoxic resistant Long-term hypoxia upregulated-circHIPK3 gastric cancer (HRGC) cell lines we established previously, which were tolerant to 2% O2 conditions, were used as the long-term hypoxia model. We found that circHIPK3 was upregulated by HIF-2α in HRGC cells, and circHIPK3 facilitated the migration and invasion ability of HRGC cells. Further investigation proved that circHIPK3 promoted metastasis of HRGC cells directly by interacting with miR-653-5p and miR-338-3p to relieve the suppression of neuropilin 1 (NRP1), resulting in the activation of downstream ERK and AKT pathways. Our study identified oncogene functions of circHIPK3 under a long-term hypoxic microenvironment and the possibility of using circHIPK3 as a potential biomarker of long-term hypoxia in GC. In conclusion, circHIPK3 could promote GC metastasis via the miR-653-5p/miR-338-3p-NRP1 axis under a long-term hypoxic microenvironment.